Sound localization with bilateral cochlear implants in noise: How much do head movements contribute to localization?. (January 2014) - Mueller, Martin F; Meisenbacher, Katrin; Lai, Wai-Kong; Dillier, Norbert
<x content-type="archive" xml:space="preserve">Abstract</x> Bilateral cochlear implant (CI) users encounter difficulties in localizing sound sources in everyday environments, especially in the presence of background noise and reverberation. They tend to show large directional errors and front–back confusions compared to normal hearing (NH) subjects in the same conditions. In this study, the ability of bilateral CI users to use head movements to improve sound source localization was evaluated. Speech sentences of 0.5, 2, and 4.5 seconds were presented in noise to the listeners in conditions with and without head movements. The results show that for middle and long signal durations, the CI users could significantly reduce the number of front–back confusions. The angular accuracy, however, did not improve. Analysis of head trajectories showed that the CI users had great difficulties in moving their head towards the position of the source, whereas the NH listeners targeted the source loudspeaker correctly.